2014
DOI: 10.1063/1.4885778
|View full text |Cite
|
Sign up to set email alerts
|

Fractal dimension computation from equal mass partitions

Abstract: While the numerical methods which utilizes partitions of equal-size, including the box-counting method, remain the most popular choice for computing the generalized dimension of multifractal sets, two massoriented methods are investigated by applying them to the one-dimensional generalized Cantor set. We show that both mass-oriented methods generate relatively good results for generalized dimensions for important cases where the box-counting method is known to fail. Both the strengths and limitations of the me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Nevertheless, these preliminary results, which are potentially sensitive to the numerical resolution of the code, would require more studies to be fully confirmed. Other approaches based on equal mass partitions [36] may provide further information on the low-density regions. to ω −1 J (standard scaling with β = 1) for an N-body simulation with initial condition similar to that used for the Vlasov case.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these preliminary results, which are potentially sensitive to the numerical resolution of the code, would require more studies to be fully confirmed. Other approaches based on equal mass partitions [36] may provide further information on the low-density regions. to ω −1 J (standard scaling with β = 1) for an N-body simulation with initial condition similar to that used for the Vlasov case.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we applied mass-oriented methods, all of which may be considered variants of the method originally proposed by van de Water and Schram [18]. In general, mass-oriented methods have advantages over size-oriented methods on low-density regions and are therefore more suitable for studying void structure formation [19]. Mass-oriented methods are based on the statistics of the k th nearest distances from reference points sampled from a given set.…”
Section: Fractal Analysismentioning
confidence: 99%
“…When the value of k is fixed with some small integer, the method is often referred to as the near neighbor method in the literature with a special case, called the nearest neighbor method, for k = 1 [20]. The near-neighbor method is also known to be problematic when estimating the generalized dimensions in the positive range of q, or equivalently, the Dimension Function in the negative range of γ [19]. The theoretical range where the singularities exist is for k < γ D(γ) .…”
Section: Fractal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The second approach is realized in the near-neighbor [22] and k-neighbor [23] methods and has the advantage of only including occupied cells in the partition. Recently, to gain insight concerning their useful regimes, we have applied these methods to standard sets with well-characterized fractal properties [24].…”
Section: Multifractal Analysis Of Simulationsmentioning
confidence: 99%